Effect of Filmless Imaging on Utilization of Radiologic Services with a Two-stage, Hospital-Wide Implementation of a Picture Archiving and Communication System: Initial Experience of a Fee-for-Service Model - Yu-Ting Kuo; Hui-Chen Chu; Tsyh-Jyi Hsieh; I-Chan Chiang; Gin-Chung Liu (Kaohsiung Journal of Medical Sciences, 2003)
A medium-sized general hospital using a fee-for-service model implemented a hospital-wide picture archiving and communication system (PACS) in two stages. This study evaluated the reporting time with filmless operation and the effect of filmless imaging on referring physicians' use of the radiologic service before and after completion of the second stage of PACS implementation. The relationship between the total number of hospital patients and the number of radiologic department patients was also evaluated. All sample images were retrieved from the PACS. All corresponding reports except for one for a computerized tomography study were available. The median reporting time for different studies performed during working hours was less than 2 hours. There was a significantly positive and linear relationship (p < 0.01) between the total number of hospital patients and the number of radiologic department patients after hospital-wide implementation of PACS. We conclude that the fee-for-service model had no negative impact on referring physicians' use of radiologic services in a filmless hospital.